Do rapid comprehensive urine drug screens change clinical management in children?. (21st October 2017) - Christian, Michael R.; Lowry, Jennifer A.; Algren, D. Adam; Thornton, Stephen L.; Deng, Shuang; Garg, Uttam
Abstract: Context: Multiple studies have concluded that urine drug screens rarely change clinical management. The rapid comprehensive urine drug screen (RCUDS) at our institution detects over 300 substances using a combination of EIA and GC/MS and typically takes 2–5 h for completion. Objective: We sought to determine whether this RCUDS altered management in the pediatric population. Methods: All patients >1 month and <18 years of age in which a RCUDS was completed from 1 January 2012 to 31 December 2012 were eligible for the study. Assuming that clinical management would not be altered in at least 90% of cases with a confidence interval of 95%, an alpha error of 5%, we calculated a sample size of 122 cases to ensure adequate study power. Four board-certified medical toxicologists reviewed 160 cases. Cases were assigned to the toxicologists based on a random-number generator. In addition, each toxicologist reviewed 12 random cases from the other three toxicologist's cases to determine inter-rater reliability. All four toxicologists reviewed any case in which a RCUDS was believed to have changed management. Results: A total of 908 RCUDS were performed during the study period, and 160 were selected for study. Mean age was 10.5 years; male = 83, female = 77. Most were ordered from the ED (101/160 = 63%), followed by the inpatient unit (36/160 = 23%), outpatient (14/160 = 9%), and ICU (9/160 = 6%). 111/160 (69%) had a history of ingestion. Of the 160 randomly chosen cases, only three cases were found in which overall clinical management was altered based on the results of the RCUDS. All three cases were children <3 years old with a RCUDS positive for amfetamines. In all the three cases, police, Division of Family Services (DFS), and social work were involved. In no case did the acute clinical management change occurred due to the results of the RCUDS. Conclusions: The RCUDS rarely changed management in patients at our institution. Further study is warranted.